2022
DOI: 10.3390/ijms232314522
|View full text |Cite
|
Sign up to set email alerts
|

Acid-Switchable Synthesis of Trifluoromethylated Triazoles and Isoxazoles via Reaction of CF3-Ynones with NaN3: DFT Study of the Reaction Mechanism

Abstract: A detailed study of the reaction of CF3-ynones with NaN3 was performed. It was found that the reaction permits the selective synthesis of either 4-trifluoroacetyltriazoles or 5-CF3-isoxazoles. The chemoselectivity of the reaction was switchable via acid catalysis. The reaction of CF3-ynones with NaN3 in EtOH produced high yields of 4-trifluoroacetyltriazoles. In contrast, the formation of 5-CF3-isoxazoles was observed under catalysis by acids. This acid-switchable procedure can be performed at sub-gram scale. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 69 publications
0
2
0
Order By: Relevance
“…It is now well established that theoretical methods are an efficient multipurpose tool for chemistry, biochemistry, and material science. Recent scientific efforts have shown that they can help us understand various phenomena, for example, reaction mechanisms or reactivity [ 35 , 36 , 37 , 38 ], electron density distribution [ 39 , 40 , 41 ], and elusive structure of complex biochemical systems or radical centers [ 42 , 43 , 44 ], anticancer [ 35 , 45 ] and antioxidant properties [ 46 , 47 , 48 , 49 , 50 , 51 ], soot formation [ 52 ] or pesticide decomposition [ 53 ]. The exchange coupling between paramagnetic centers has been a subject of such investigations at the density functional theory (DFT) and ab initio levels, but these studies were mainly limited to the interaction between metallic centers [ 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is now well established that theoretical methods are an efficient multipurpose tool for chemistry, biochemistry, and material science. Recent scientific efforts have shown that they can help us understand various phenomena, for example, reaction mechanisms or reactivity [ 35 , 36 , 37 , 38 ], electron density distribution [ 39 , 40 , 41 ], and elusive structure of complex biochemical systems or radical centers [ 42 , 43 , 44 ], anticancer [ 35 , 45 ] and antioxidant properties [ 46 , 47 , 48 , 49 , 50 , 51 ], soot formation [ 52 ] or pesticide decomposition [ 53 ]. The exchange coupling between paramagnetic centers has been a subject of such investigations at the density functional theory (DFT) and ab initio levels, but these studies were mainly limited to the interaction between metallic centers [ 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 ].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, we have proposed convenient syntheses of α-CF 3 -β-aryl enamines [ 31 ], α,β-diaryl-CF 3 -enones [ 32 ] and CF 3 -ynones [ 33 ], which appeared to be versatile CF 3 -building blocks for the synthesis of various fluorinated compounds [ 34 , 35 ]. Recently, we have found that reaction of CF 3 -ynones with sodium azide can be used for directed synthesis of either 5-CF 3 -isoxazoles or previously unknown 4-trifluoroacetyltriazoles [ 36 ]. The prepared triazoles are a new class of triazolyl compounds.…”
Section: Introductionmentioning
confidence: 99%